Enantioselective Synthesis of Tertiary β‐Boryl Amides by Conjunctive Cross‐Coupling of Alkenyl Boronates and Carbamoyl Chlorides. Issue 15 (18th February 2022) - Wilhelmsen, Christopher A.; Zhang, Xuntong; Myhill, Jesse A.; Morken, James P.
Abstract: Synthesis of versatile β tert ‐boryl amides is accomplished by conjunctive cross‐coupling of α‐substituted alkenyl boron "ate" complexes and carbamoyl chloride electrophiles. This reaction can be accomplished in an enantioselective fashion using a palladium catalyst in combination with MandyPhos. The addition of water results in enhanced chemoselectivity for the conjunctive coupling product relative to the Suzuki–Miyaura cross‐coupling product. Transformations of the reaction products were examined as well as application to the synthesis of (+)‐adalinine. Abstract : Versatile tertiary β‐boryl amides are prepared by conjunctive cross‐coupling of α‐substituted alkenyl boron "ate" complexes and carbamoyl chloride electrophiles. This reaction gives morpholine amides, which are easily converted to an array of useful building blocks.